Volatile organic compound emissions from the human body: Decoupling and comparison between whole-body skin and breath emissions. (December 2022) - Zou, Ziwei; Yang, Xudong
Abstract: The human body can affect indoor air by emitting volatile organic compounds (VOCs) through breath and skin. However, studies on the quantitative characteristics of skin VOC emissions are scarce compared to those on the characteristics of breath emissions. Moreover, the species and emission rates of VOCs emitted from the breath and whole-body skin of a single person have rarely been reported. In this study, VOCs emitted from the whole-body skin and breath of 14 young adults under controlled conditions were decoupled and measured. The number of VOC species emitted from each study participant's whole-body skin and breath ranged 38–69 and 28–55, respectively, with total emission rates of all detected VOCs of 164–518 and 286–1030 μg/h, respectively. The VOCs in the high-detection rate intervals also had higher emission rates, increasing their importance in human body emissions. There were 9–26 common VOCs and 25–47 different VOCs between the skin and breath emissions. Acetone was detected in both the skin and breath emissions of all study participants, with the highest emission rate in each participant's whole-body emissions. Ketones, siloxanes, aldehydes, and alcohols contributed the most to the whole-body skin emission rates of each study participant, whereas ketones and alkenes alone accounted for most of the breath emission rates. Analysis of the generation mechanisms found that endogenous and exogenous VOCs were dominant in breath and skin emissions, respectively. These results can enrich the qualitative and quantitative characteristics of breath and skin emissions and improve understanding of emission mechanisms. Highlights: VOC species and emission rates of the same person's breath and skin were compared. Acetone had the highest emission rate for both breath and skin emissions. Endogenous and exogenous VOCs dominated breath and skin emissions, respectively. Emission rates of 42 VOCs from whole-body skin, breath, and whole body were compared.